ANALISIS PENGARUH JUMLAH ANGKATAN KERJA DAN POPULASI TERHADAP PENGELUARAN PEMERINTAH DI LIMA NEGARA INDUSTRI MAJU - Amanda, Sephia Rizki; Samsudin, M.Afdal (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
This study aims to empirically investigate the impact of the labor force and population on government expenditure as a percentage of Gross Domestic Product (GDP) in five selected developed countries: the United States, the United Kingdom, New Zealand, Germany, and Australia. The research employs secondary quantitative data sourced from the World Bank and other official institutions, which are subsequently analyzed using multiple linear regression with a panel data approach. The analysis includes descriptive statistics, presented through tables and graphs, and inferential statistics to examine the significance of the independent variables' effects on the dependent variable. The empirical findings reveal that both the labor force and population exert a statistically significant influence on government expenditure as a percentage of GDP, both individually and collectively. These results underscore the relevance of demographic and workforce dynamics in shaping fiscal policy across developed economies.Keywords: Labor Force, Population, Government Expenditure, Multiple Linear Regression, Panel Data.